Ammonia powered thermal-responsive smart window with spectral regulation of Cu2+ and sodium copper chlorophyllin - Pu, Jihong; Shen, Chao; Lu, Lin; Long, Yi; Zhang, Chunxiao; Shuai, Yong; Kalogirou, Soteris A. (My University, 2024)
Thermal responsive windows are highly promising for the next-generation architecture for their self-powered solar transmittance. However, existing thermochromic techniques, include VO2- and hydrogel-based systems, have not been used for large-scale in window applications, because of the technical obstacles such as low luminous transmittance (Tlum), poor solar modulation ability (ΔTsol), high transition temperature (Tc) and high haze rate. To tackle those issues, a new thermal-responsive design, i.e., the Ammonia Pressure Powered smart (APPs) window, was proposed, with Cu2+ and sodium copper chlorophyllin (SCC) providing solar spectrum management. In comparisons to traditional thermochromic windows, the new concept of APPs window shows significant energy-related advances. Particularly, a feasible Tc (24–36 °C), outstanding ΔTsol (67 %), and high Tlum in both cold (84 %) and hot (47.4 %) states are reported in this study. In addition, outdoor experimental test of the APPs window demonstrated that it could produce a rational daylight level of both photopic effects and melanopic effects, whilst reduce the room temperature by about 4 °C on hot sunny day. Furthermore, energy simulations conducted for the APPs window in three different cities (Singapore, Hong Kong and Harbin) indicate its superior performance, compared to the double-layered low-e glazing windows, across various climatic conditions. With cost-effective materials and excellent performance, the authors believe that this new APPs window represents a smart and sustainable solution for the development of next-generation green buildings.
Keywords: Ammonia pressure powered; Broadband solar spectrum management; Building energy saving; Thermal-responsive smart window